THE CONTRIBUTION AND DEVELOPMENT OF ROEMAH SCHOOLAH AGAMA-ISLAM KEDIRI 1959-1991 - Jauhari, Muhammad Thonthowi; Afiyanto, Hendra (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
ABSTRACTEducation in the Dutch East Indies has undergone significant development since the implementation of ethical politics. Nonetheless, the Dutch government's education model faced criticism from the Budi Utomo association for not meeting the needs of the indigenous community. This led to the establishment of political and Islamic schools, including the Roemah Schoolah Agama-Islam Kediri. The research aims to answer three problem formulations. Firstly, what is the history behind the establishment of Roemah Schoolah Agama-Islam Kediri? Secondly, what are the dynamics of the development of Roemah Schoolah Agama-Islam during 1959-1991? Thirdly, what contribution has Roemah Schoolah Agama-Islam made to the progress of Islamic education in Kediri? This study aims to investigate the history and evolution of Roemah Schoolah Agama-Islam and its impact on the advancement of Islamic education in Kediri. The research utilises historical methodology, including the stages of heuristics, verification, interpretation, and historiography, to achieve its objectives. Some of the findings include: first, Roemah Schoolah Agama-Islam was founded by Raden H. Alimoestoha and H. Sjakur on 18 March 1919; second, in the development of learning at Roemah Schoolah Agama-Islam Kediri there are dynamics that cause changes in the name and level of the school; third, the movement at Roemah Schoolah Agama-Islam contributed to the advancement of Islamic education in Kediri.Keywords: Islamic Education, Roemah Schoolah Agama-Islam, YBWPI.Â ABSTRAKPendidikan di Hindia Belanda mengalami perkembangan masif sejak diberlakukannya politik etis. Dalam pelaksanaan kebijakan politik etis pemerintah Belanda mendirikan beberapa sekolah yang diperuntukan untuk anak-anak bumiputra, namun penyelenggaraan pendidikan oleh pemerintah Belanda mendapatkan kritik dari perkumpulan Budi Utomo karena dianggap tidak sesuai dengan kebutuhan masyarakat bumiputra. Kritik Budi Utomo berdampak pada berdirinya sekolah-sekolah partikelir bercorak politik dan agama Islam, salah satunya adalah Roemah Schoolah Agama-Islam Kediri. Pada penelitian ini terdapat tiga rumusan masalah, pertama, bagaimana sejarah berdirinya Roemah Schoolah Agama-Islam Kediri? kedua, bagaimana dinamika perkembangan Roemah Schoolah Agama-Islam tahun 1959-1991? ketiga, apa kontribusi Roemah Schoolah Agama-Islam terhadap kemajuan pendidikan Islam di Kediri? Penelitian ini bertujuan untuk mengetahui sejarah dan perkembangan Roemah Schoolah Agama-Islam dan kontribusinya bagi kemajuan pendidikan Islam di Kediri. Penelitian ini menggunakan metode penelitian sejarah dengan tahapan heuristik, verifikasi, intepretasi, dan historiografi. Beberapa hasil temuan antara lain: pertama, Roemah Schoolah Agama-Islam didirikan oleh Raden H. Alimoestoha dan H. Sjakur pada 18 Maret 1919, kedua, dalam perkembangan pembelajaran di Roemah Schoolah Agama-Islam Kediri terdapat dinamika yang menyebabkan perubahan nama dan jenjang sekolah, ketiga, pergerakan di Roemah Schoolah Agama-Islam ikut andil dalam kemajuan pendidikan Islam di Kediri.Kata Kunci: Pendidikan Islam, Roemah Schoolah Agama-Islam, YBWPI.